Effect of Arc Power on the Wear and High-temperature Oxidation Resistances of Plasma-Sprayed Fe-based Amorphous Coatings - Luo, Jinheng; Shi, Na; Xing, Ya-Zhe; Jiang, Chaoping; Chen, Yongnan (High temperature materials and processes, 2019)
Atmospheric plasma spraying (APS) technique is employed to prepare Fe-based amorphous coatings on T91 steel substrate under various arc powers of 30 kW, 35 kW and 40kW. The morphology and microstructure of both Fe-based powders and amorphous coatings are characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). In addition, the wear resistance and high-temperature oxidation resistance of the plasma-sprayed coatings at various arc powers are studied. It is found that with increasing the arc power, the content of the porosity and the amorphous phase in the coatings declines. Specifically, under 30 kW, 35 kW and 40 kW arc power, the porosity of the coatings is 7.96%, 6.13% and 5.75%. Correspondingly, the relative content of amorphous phase from the coatings is measured to be 96.07% (mass fraction), 73.89% and 65.54%. Moreover, under 40 kW arc power, it gives the coating the highest micro-hardness having more compact microstructure and more dispersive -Fe grains. Besides, the coatings fabricated at high arc power exhibit less wear induced weight loss and less weight gain from high-temperature oxidation comparing with those fabricated at lower arc power.